Estudos da fauna de Chironomidae (Diptera) nos córregos galharada, campo do meio e casquilho do parque estadual de Campos do Jordão, SP - Suriano, Marcia Thais (2003)
Chironomidae is an important group among the aquatic Diptera significantly participating in the composition of the benthic macroinvertebrate community of a vaariety of aquatic systems. It has been estimated that there exists at least 2.000-3.000 species in each biogeographical region. In Brazil, however, there are few studies on the ecology and taxonomy of this group. In Sao Paulo State 89 genera and 66 species were registered so far. Aiming to contribute to the advance in the knowledge on this family, the present work analized the Chironominae occurring at the State Park of Campos de Jordao, considering the absence of data regarding this family for that region which has peculiar characteristics for Sao Paulo State, such as: high altitude and subtropical high a altitude temperate climate. Samplings for the immature phase were performed by using a Surber type sampler and a D net. The samples were taken at the rivers Galharada and its affluent, Campo do Meio and Casquilho, all them of low order, with stony beds, protected by riparian vegetation; The water is transparent, cold, well oxygenated, acid, with low electrical conductivity and turbidity. Adults were captured close to the sampling points of the larvae using light trap. The results revealed differences in the structure of the communities among the streams. From cluster analysis it was possible to see the clustering of Galharada sampling points located in a central region of the park and mainly represented by the taxa aff.Omisus sp1 and Corynoneura. On the other hand the sampling points Campo do Meio and Casquilho, suffering anthropogenic impacts presented a dominance of aff. Pseudochironomus sp1 species. The diversity of adult specimens was higher than that of larvae, and new records of species for Sao Paulo State were found (Neelamia) and Brazil (Paramerina), as well as new species (Antillocladius sp1 and Goeldichironomus sp). The faunistic data will be incorporated and made available by the Environmental Information System é SinBiota/FAPESP.